2004
DOI: 10.2172/918739
|View full text |Cite
|
Sign up to set email alerts
|

Rapid inactivation of SARS-like coronaviruses.

Abstract: Chemical disinfection and inactivation of viruses is largely understudied, but is very important especially in the case of highly infectious viruses. The purpose of this LDRD was to determine the efficacy of the Sandia National Laboratories developed decontamination formulations against Bovine Coronavirus (BCV) as a surrogate for the coronavirus that causes Severe Acute Respiratory Syndrome (SARS) in humans. The outbreak of SARS in late 2002 resulted from a highly infectious virus that was able to survive and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Additionally, the clinical respiratory tract infections show similarities [30]. Because of all these resemblances, BCoV has already been suggested and successfully employed as a SARS-CoV(-2) surrogate in many different applications [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the clinical respiratory tract infections show similarities [30]. Because of all these resemblances, BCoV has already been suggested and successfully employed as a SARS-CoV(-2) surrogate in many different applications [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Since coronaviruses, and therefore SARS-CoV-2, have an envelope, they should be in group A, according to the Klein and Deforest classification system, as shown in Table 2. Thus, SARS-CoV-2 might allow the penetration of lipophilic antimicrobials such as halogens, aldehydes, quaternary ammonium compounds (QAC), phenolics, alcohols, peroxides, proteases, and detergents [57]. Srivastava et al examined the effectiveness of various malaria drugs against SARS-CoV-2 and found that the more lipophilic the drug, the better it can penetrate the virus and inhibit it.…”
Section: Lipophilicitymentioning
confidence: 99%
“…However, when treatment levels were increased to 2,100 ppm NaOCl) on stainless steel coupons, a ≥4.5 log 10 TCID50/mL reduction was achieved after 30 s against the SARS-CoV-1 surrogate, MHV (Dellanno et al, 2009). Much lower concentrations were required in seeded hospital wastewater; SARS-CoV-1 was inactivated by exposure to 10 ppm NaOCl (0.4 ppm free chlorine) after 10 min exposure, while inactivation occurred within 1 min in 20 ppm NaOCl (0.5 ppm free chlorine; Kott et al, 1975;Rutala and Weber, 1997;Kapil et al, 2004;Wang et al, 2005;Dellanno et al, 2009;Geller et al, 2012;Kumar et al, 2017;Chin et al, 2020).…”
Section: Sodium Hypochloritementioning
confidence: 99%